Detasseling anticipation in corn and its effects on leaf area, seed production and seed quality - Menezes, Niilson Lemos de; Cícero, Silvio Moure (Pesquisa Agropecuaria Brasileira, 1994)
The aim of the present work was to study the effects of early detasseling on leaf area, seed production and the quality of corn seed. An essay with single hybrids - the parents of the double hybrid AG 405 - was installed in the experimental area of the "Companhia Sementes Agroceres S.A.", in the city of Santa Cruz das Palmeiras, SP, during the crop season of 1988/89. The treatments consisted in detasseling the plants at 49, 52, 54, 57 and 61 days after sowing. For the hybrids studied the normal time of detasseling was considered 57 days, when two or three leaves were involving the tassel. In each plot were determined, the number of normal and broken or lodged plants, healthy and damaged ears, leaf areas (before and after detasseling), number of cut leaves per plant during the detasseling, fresh and dry matter and its components, seed production, physiological quality and the chemical composition of seeds. It was concluded that the anticipation of detasseling in female plants of the hybrid AG 405, in relation to the normal time of detasseling, progressively reduces the leaf area and significantly decreases the seed production when the anticipation is larger than three days, but does not affect the chemical composition and the quality of seeds. The number of the ears is the component of yield more affected by detasseling anticipation and that contributes more for the variation on the seed production.